Identification of the risk factors of neonatal macrosomia in EHS «Nouar Fadéla », Oran - Algeria - Djamila Bouabida; Amina Dida; Fatiha Belaoun; Raouida Mecifi; Feroudja Djeghali; Nassima Makhlouf; Feroudja Graine; Malika Benbouabdelah (Journal de la Faculté de Médecine d'Oran, 2022)
Introduction - A newborn is said macrosome if the birth weight is higher than the 90th percentile according to the reference curves. It is a population at risk exposed to neonatal complications that can compromise the vital prognosis and / or functional. The objective of this study was to estimate the hospital prevalence of macrosomia and to identify the risk factors for its occurrence.